The Perspective of Indonesian Teachers on the Google Classroom Usage in Blended Teaching - Fatimatus Suhroh; Bambang Yudi Cahyono (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: Google Classroom is a kind of platform that teachers and students have come to know about. One of the learning processes achieved with google classroom is to blend the style of learning. Blended teaching is one of the teaching processes which is done not only inside the class (offline) but also outside the class (online). The study aims to impose the perspective of Indonesian teachers on the usage of Google Classroom. The study is performed through a qualitative research design. The sample of the study, which uses a survey method through a google form, consisting of forty teachers throughout Indonesia who have administered Google Classroom in their classroom for at least one semester. The data acquired has been put through a comprehensive analysis by categorizing and highlighting the data. The findings showed that almost all the teachers used blended teaching and it had three of the most beneficial usage which is accessibility, as a means of communication and data analysis. The significant challenges on the usage of Google Classroom were in the internet connection and online submitted assignments. They assumed that the overall highlights on Google Classroom usage can be effective and improved for future features. Abstrak: Google Classroom adalah sebuah platform yang banyak diketahui oleh para guru dan siswa. Salah satu proses pembelajaran yang dicapai dengan google classroom adalah untuk memadukan gaya belajar. Pembelajaran campuran (blended learning)  adalah salah satu proses pengajaran yang dilakukan tidak hanya di dalam kelas (offline) tetapi juga di luar kelas (online). Penelitian ini bertujuan untuk mengetahui perspektif guru Indonesia tentang penggunaan Google Classroom. Penelitian dilakukan melalui desain penelitian kualitatif. Sampel penelitian, yang menggunakan metode survei menggunakan google form, terdiri dari empat puluh guru di seluruh Indonesia yang telah menerapkan Google Classroom di kelas mereka selama setidaknya satu semester. Data yang diperoleh telah dimasukkan melalui analisis yang komprehensif dengan mengategorikan dan menganalisis pokok data. Temuan menunjukkan bahwa hampir semua guru menggunakan pengajaran campuran dan memiliki tiga penggunaan yang paling bermanfaat yaitu aksesibilitas, sebagai sarana komunikasi dan analisis data. Tantangan yang signifikan dalam penggunaan Google Classroom adalah dalam koneksi internet dan penugasan yang dikirimkan secara online. Mereka berasumsi bahwa sorotan keseluruhan pada penggunaan Google Classroom dapat efektif dan ditingkatkan untuk fitur di masa depan.